An in vivo comparative study of pure Mg and Mg-Zn alloy plates implanted in the mandible of New Zealand rabbits - Mohammed, Altaib Abdel Razik; Alghonemy, Wafaa Yahia; Sarhan, Naglaa I.; Abdal-hay, Abdalla; Saleh, Reda Gaber (Journal of oral biology and craniofacial research (Amsterdam), 2025)
Biodegradable magnesium-based implants present significant potential for maxillofacial applications, particularly in mandible fixation, due to their osteoconductive properties and elimination of secondary removal surgeries. The present study aimed to assess the in vivo biocompatibility and degradation behavior of pure magnesium (Mg) and Mg-Zn-Ca alloy plates implanted in the mandibles of New Zealand rabbits, providing insights into their clinical viability. Twenty-four male New Zealand White rabbits were divided into two groups and received titanium, pure Mg, and Mg-Zn-Ca alloy plates passively implanted into the mandibular bone surface. Animals were evaluated histologically and radiographically at 4 and 8 weeks postoperatively. Histomorphologic analysis demonstrated that all implants showed clinical stability throughout the observation period. While no signs of inflammation were observed in the pure Ti and pure Mg groups, the Mg-Zn-Ca alloy group exhibited moderate to severe inflammatory cell infiltration at 4 weeks and localized bone resorption at 8 weeks, as confirmed histologically. Remarkably, new bone formation was observed surrounding the Mg implants, with no evidence of fibrous capsule development. Mg-Zn-Ca biodegradation had no adverse systemic effects as the histological evaluations using H&E staining of major organs revealed no significant abnormalities. Mg-based materials show promise for maxillofacial fixation applications due to their osteogenic potential and biodegradability. However, the observed inflammatory responses and soft tissue effects highlight the need for further optimization of alloy composition and degradation control before clinical translation.